Observation of Anesthetic Effect of Dexmedetomidine Combined With Intraspinal Anesthesia in Hip Arthroplasty and its Effect on Postoperative Delirium and Stress Response - Shen, Yading; Wang, Chenyu; Zhong, Xiaoping; Wu, Yandan; He, Xiaoxia (Frontiers in Surgery, 2022)
Objective: To observe the anesthetic effect of dexmedetomidine combined with spinal anesthesia in hip arthroplasty, and to analyze the effects of dexmedetomidine on postoperative stress response, incidence of delirium, immune function and inflammatory indicators. Methods: A total of 42 patients who underwent hip replacement in our hospital from March 2020 to June 2021 were selected as the research subjects and randomly divided into the control group and the observation group, 21 cases in each group. The control group was given intraspinal anesthesia, and the observation group was given dexmedetomidine on this basis. The onset time and maintenance time of sensory and motor nerve block were recorded. Stress response indexes [cortisol (Cor), blood glucose (Glu), adrenaline (E), noadrenaline (NE)], T lymphocyte subsets (CD3+, CD4+, CD8+, CD4+/CD8+), inflammatory indexes [tumor necrosis factor -α (TNF-α) and interleukin-6 (IL-6)] were detected before and after operation, and the incidence of postoperative delirium in both groups was recorded. Results: The onset time of sensory nerve block and motor block in the observation group were lower than those in the control group, and the retention time of sensory nerve block and motor nerve block were higher than those in the control group (P<0.05). After surgery, the levels of Cor, Glu, E and NE in the observation group were lower than those in the control group (P<0.05). After surgery, the incidence of postoperative delirium in the observation group (4.79%) was lower than that in the control group (28.57%) (P<0.05). After surgery, the levels of CD3+, CD4+, CD8+, and CD4+/CD8+ in the observation group were higher than those in the control group (P<0.05). After surgery, the levels of TNF-α and IL-6 in the observation group were lower than those in the control group (P<0.05). Conclusion: The combined use of dexmedetomidine and intraspinal anesthesia has good anesthesia effect in hip joint replacement, which can greatly reduce the stress response of patients, reduce the incidence of postoperative delirium, and effectively restore the immune function of patients, reduce the level of inflammatory response, and has high clinical application value.